The Influence of Attitudes and Subjective Norms of Domestic Millennial Tourists on the Intention to Stay at An Environmentally-Friendly Hotel - Febrianto, I Gusti Agung; Anggani, Mayang Fitri; Pinaria, Ni Wayan Chintia (Journal of Tourism Sustainability, 2024)
This research aims to determine the influence of domestic millennial tourists' attitudes and subjective norms on their intention to stay at an environmentally friendly hotel. Attitude is the result of a psychological process that cannot be observed directly, but must be inferred from what is said or done. Attitudes towards environmentally friendly products are a relevant subject. Subjective norms are a person's beliefs regarding expectations which are influenced by other parties, both individually and in groups, to perform or not perform a particular behavior. Intention is an indicator of the extent to which people are willing to carry out a specific behavior or a person's willingness to carry out a certain behavior. This research focuses on domestic millennial tourists, consisting of 100 respondents. The data were analyzed with multiple regression statistical technique resulting a positive and significant influence of the attitude and subjective norm variables on the intention to stay at an environmentally friendly hotel. It was investigated that domestic millennial tourists are highly concerned about environmentally friendly hotel to be selected as their accommodation and it was also found out that they obtain direct influence from their closest relatives in determining the choice of environmentally friendly hotels